2009
DOI: 10.2174/092986709787458470
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Molecular Ultrasound Imaging: Concepts and Contrast Agents

Abstract: Contrast-enhanced ultrasound has shown convincing results for monitoring vessel morphology, surrogate markers of vascularization and changes in molecular marker expression in oncological and cardiovascular diseases. Ultrasound contrast agents have the ability to increase the backscattering signal intensity of an ultrasound pulse. An interesting class of ultrasound contrast agents are gas filled microbubbles, which can be synthesized by external bubble encapsulation using sugar matrices or microspheres consisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
99
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(101 citation statements)
references
References 0 publications
1
99
0
1
Order By: Relevance
“…Gas-filled microbubbles are routinely used to enhance the contrast of tumors and for the functional assessment of vascularization (11,12). In this context, functional assessment includes the visualization of vessels and the quantification of blood velocity, perfusion and relative blood volume (rBV).…”
Section: Introductionmentioning
confidence: 99%
“…Gas-filled microbubbles are routinely used to enhance the contrast of tumors and for the functional assessment of vascularization (11,12). In this context, functional assessment includes the visualization of vessels and the quantification of blood velocity, perfusion and relative blood volume (rBV).…”
Section: Introductionmentioning
confidence: 99%
“…The reperfusion of these contrast agents is observed and signals are fit to models to estimate spatially resolved reperfusion times. [13][14][15] While the destruction-reperfusion ultrasound imaging technique is a powerful means of imaging tissue perfusion, some work has shown that the destruction of microbubbles may damage microvascular walls. 16,17 Other preclinical methods of measuring perfusion rates such as dynamic contrast-enhanced MRI also typically require contrast agents and are not sufficiently low cost or high throughput for widespread screening tasks.…”
Section: Introductionmentioning
confidence: 99%
“…In the destructive mode with pulsed waves the shell of the microbubble even cracks and the gas is emitted explosively, enhancing the ultrasound backscatter. To increase their selectivity, targeted ligands like peptides or antibodies have been conjugated to the surface of microbubbles to assess for example processes of inflammation or angiogenesis (Klibanov, 2006;Kiessling et al, 2009). This approach has improved the properties of ultrasound up to a molecular imaging technique.…”
Section: Ultrasoundmentioning
confidence: 99%